Approving of but not choosing violence: paths of nonviolent radicals - Jaskoski, Maiah (Terrorism and political violence, 2020)
Why do some political radicals—people who believe in using violence for political ends and who may sympathize with local violent groups—not themselves perform violent acts or join violent organizations? This article finds that prior research on terrorism, insurgency, civil war, and ethnic conflict seems to do a poor job of predicting who upon adopting radical political views will actually engage in violence. In fact, there is a great deal of contingency involved in the choice of whether or not to become violent. Employing path dependence, the article treats the radicalizing moment as a “critical juncture,” filled with contingency, but after which actions become more predictable: during this small window of time, radicalized individuals might happen to choose a profession and/or join an organization that is nonviolent, but subsequently become institutionalized as nonviolent actors. The article therefore offers an explanation for how individuals with radical beliefs can be institutionalized as either violent or nonviolent. The study’s findings are based on a content analysis of interviews with 129 nonviolent activists, most of whom exhibited radical beliefs at the time of the interview, and former violent actors, in 12 countries experiencing violent internal conflict.